THE ROLE OF BLENDED LEARNING IN TEACHING ENGLISH LANGUAGE - Matyakubov Zohid Mo’minbayevich; Masharipova Amina Ismoil qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information about The Role of Blended Learning in teaching English Language.